2011
DOI: 10.1128/jvi.01265-10
|View full text |Cite
|
Sign up to set email alerts
|

Adenovirus Membrane Penetration Activates the NLRP3 Inflammasome

Abstract: Adenovirus type 5 (Ad5) infection of macrophages results in rapid secretion of interleukin-1␤ (IL-1␤) and is dependent on the inflammasome components NLRP3 and ASC and the catalytic activity of caspase-1. Using lentivirus-expressed short hairpin RNA (shRNA) and competitive inhibitors, we show that Ad-induced IL-1␤ release is dependent upon Toll-like receptor 9 (TLR9) sensing of the Ad5 double-stranded DNA (dsDNA) genome in human cell lines and primary monocyte-derived macrophages but not in mouse macrophages. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
166
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(173 citation statements)
references
References 58 publications
6
166
0
1
Order By: Relevance
“…However, neither treatment reduced IL-1␤ production after introduction of plasmid DNA to activate the AIM2 inflammasome (Fig. 5D), consistent with the recent demonstration that these ROS scavengers have no effect upon the AIM2 inflammasome (46). These results indicate that inhibiting ROS produced by Francisella infection partially reduces the activation of the IL-1␤-producing inflammasomes, consistent with the identified role of NLRP3.…”
Section: The Il-1␤ Response Of Francisella-infected Thp-1 Cells Requisupporting
confidence: 89%
See 1 more Smart Citation
“…However, neither treatment reduced IL-1␤ production after introduction of plasmid DNA to activate the AIM2 inflammasome (Fig. 5D), consistent with the recent demonstration that these ROS scavengers have no effect upon the AIM2 inflammasome (46). These results indicate that inhibiting ROS produced by Francisella infection partially reduces the activation of the IL-1␤-producing inflammasomes, consistent with the identified role of NLRP3.…”
Section: The Il-1␤ Response Of Francisella-infected Thp-1 Cells Requisupporting
confidence: 89%
“…These differences are likely not a consequence of Francisella lipopolysaccharide (LPS). Although initial studies pointed to a stimulatory U112 LPS and a non-stimulatory LVS LPS (16,45) as a potential explanation for the above differences, later work clearly demonstrated that highly purified LPS from the U112 strain was non-stimulatory (46). Consistently, differences in the IL-1␤ response between Francisella strains were evident in all the experimental systems, including those using inflammasome-reconstituted epithelial cells.…”
Section: Discussionmentioning
confidence: 84%
“…For example, disruption of lysosomal membranes and cathepsin B release are required for NLRP3 inflammasome activation by adenovirus type 5, through penetration of endosomal membranes. 94 Group B Streptococcus-induced NLRP3 inflammasome activation also depends on hemolysin-mediated lysosomal leakage. 95 Recently, lysosomal rupture and the release of lysosomal hydrolases have been shown to be essential for albumintriggered tubulointerstitial inflammation and fibrosis, implicating lysosomal damage in the pathogenesis of chronic kidney disease through NLRP3 inflammasome activation.…”
Section: Molecular Mechanisms Of the Canonical Activation Of The Nlrpmentioning
confidence: 99%
“…Further, NLRP3-independent sensing of adenovirus was observed, in which IL-1a and b3 integrins play a crucial role in triggering an early proinflammatory immune response [71]. Another study on human macrophages showed that NLRP3 activation occurs in a cathepsin B-and ROS-dependent manner during adenovirus infection [72,73]. Infection in BMDMs with modified vaccinia virus Ankara (MVA) has demonstrated that both activation of inflammasome and transcription of IL-1b and NLRP3 are dependent on the crosstalk between TLR2-MyD88 and the NLRP3 inflammasome.…”
Section: Dna Virusesmentioning
confidence: 99%